Cabinet Reshuffles and Parliamentary No-Confidence Motions - Gonzalez-Bustamante, B (Cambridge University Press, 2024)
How do cabinet reshuffles affect the parliamentary opposition s use of no-confidence motions in the government? Opposition parties employ no-confidence motions as electoral signals to highlight government incompetence and to position themselves as a government in waiting. We argue that cabinet reshuffles - which prime ministers use to respond to policy failures, scandals, poor ministerial performance and disloyalty - present an opportunity for the opposition to deploy no-confidence motions to this end. The incentives to deploy this strategy, however, are contingent on the nature of the party system and are greatest where party-system concentration positions a single opposition party as the alternative to the government and sole beneficiary of a no-confidence vote. We test this expectation using a multilevel modelling approach applied to data on reshuffles in 316 governments and 16 parliamentary democracies, and find support for our expectation: cabinet reshuffles raise the probability of no-confidence motions conditional on party-system concentration. © © The Author(s), 2022.